A French Peruvianist in the Andes: An interview with Pierre Duviols - Itier, César (2018)
In this interview, Pierre Duviols, one of the most renowned French Peruvianists, speaks about his biographical and scholarly trajectory. He presents a detailed picture of his family environment, his studies, the origins of his interest in the history of the Andes, and his relationships with Peruvian scholars since his arrival in Peru in the mid-20th century. He also tells us of his perspectives on research and his work methodology.